Analisis Karakter Siswa Kelas Tinggi Pada Diskusi Pembelajaran PPKn SD Inpres 7/83 Pasempe - Muliadi Muliadi; Muhammad Amran; Asriadi Asriadi; Rina Bella Saputri (Phinisi Integration Review, 2022)
This research was a qualitative descriptive type that aimed to describe the high-class students character in the discussion of civic education learning at SD Inpres 7/83 Pasempe Palakka District Bone Regency. The subject in this research were students of grade IVth and Vth in SD Inpres 7/83 Pasempe Palakka District  Bone Regency, count to 27 people. Data collections technique used were observation and documents study technique. Data analysis techniques used were data reduction, data display and conclusion drawing/verification. Conclusion of this research indicated that the high-class students character in the discussion of civic education at SD Inpres 7/83 Pasempe Palakka District Bone Regency were religious, nasionalist, integrity, cooperate and independent. Penelitian ini merupakan penelitian kualitatif dengan jenis deskriptif yang bertujuan untuk mendeskripsikan karakter siswa kelas tinggi pada diskusi pembelajaran PPKn SD Inpres 7/83 Pasempe Kecamatan Palakka Kabupaten Bone. Subjek dalam penelitian ini adalah siswa kelas IV dan V SD Inpres 7/83 Pasempe Kecamatan Palakka Kabupaten Bone. Data penelitian diperoleh dari melalui observasi partisipasi pasif dan studi dokumen. Teknik analisis data yang digunakan adalah data reduction, data display, dan verification/conclusion drawing. Kesimpulan penelitian ini bahwa karakter siswa kelas tinggi pada diskusi pembelajaran PPKn di SD Inpres 7/83 Pasempe Kecamatan Palakka Kabupaten Bone menunjukkan karakter religius, nasionalis, integritas, gotong royong dan mandiri.